ACTION OF Trichoderma asperellum AND BIOACTIVE METABOLITES ON Fusarium spp., PATHOGENS OF Carya illinoinensis - Rabuske, Jéssica Emília; Brun, Thiarles; Saldanha, Mateus Alves; Martello, Laís da Silva; Mazutti, Marcio Antonio; Muniz, Marlove Fátima Brião (Floresta, 2024)
The cultivation of pecan tree [Carya illinoinensis (Wangenh.) K. Koch.] is expanding in Rio Grande do Sul state and, with that, there has been an increase in the disease reports. Among the diseases identified, there is a root rot caused by Fusarium spp. The control of phytopathogenic fungi present in the soil is difficult to obtain, and the control through antagonists such as Trichoderma spp. is a viable way of management. Thus, the objective of this work was to analyze different forms of action of Trichoderma asperellum in the control of Fusarium spp. The antagonistic action was evaluated by paring cultures, presence of volatile and non-volatile metabolites. The mycelial growth inhibition in the culture pairing ranged from 10.38% to 43.17%, while for volatile metabolites protection was lower, reaching values of a maximum of 14.54%. As for the non-volatile metabolites, a percentage of inhibition varied from zero for some treatments to 44.99% in the control of Fusarium graminearum. T. asperellum inhibited the growth of Fusarium spp. through different studied modes of action.